الحساب الفرعي للمؤسسات غير الربحية دراسة تحليلية في ضوء الدليل الأممي والتجربة الكندية: The Satellite Account for Nonprofit Institutions: An Analytical Study in Light of the UN Handbook and the Canadian experience - عبد القيوم بن عبد العزيز الهندي, (Journal of North African Economies, 2025)
This study aims to analyze the conceptual and methodological framework of the satellite account for nonprofit institutions as outlined in the United Nations Handbook, review the Canadian experience as a pioneering applied model, and explore the prospects of developing quantitative and qualitative indicators to measure the contribution of the charitable sector to the macroeconomy within Islamic contexts. The research addresses a growing need to establish a statistical representation of the charitable sector in Arab and Islamic countries, where its role is expanding while statistical tools remain limited in capturing its economic and social impact. The study adopts a descriptive-analytical methodology and is structured into three main chapters. The first chapter examines the foundational principles and justifications presented in the UN Handbook for establishing a satellite account for nonprofit institutions, alongside the recommended implementation models and prerequisites. The second chapter presents the Canadian experience, detailing the account’s evolution, classification methods, data sources, voluntary work valuation, output tables, and lessons learned. The third chapter explores the rationale, benefits, and requirements for implementing such an account in Arab and Islamic countries, proposes context-specific measurement domains aligned with Islamic economic principles, and introduces a set of applicable quantitative and qualitative indicators. The study concludes that operationalizing a satellite account for the charitable sector provides a valuable opportunity to enhance its integration into national economic policies. Achieving this goal requires developing a unified classification system, building integrated data infrastructures, fostering institutional partnerships, and designing tailored indicators that reflect the sector’s ethical, legal, and social distinctiveness. Keywords: Satellite account, charitable sector, nonprofit institutions, Islamic economics, quantitative and qualitative indicators, Canadian experience, UN Handbook.